2.1: Invited Paper: Dependence of Illumination Level on Phantom Array Effect. (24th February 2021) - Wang, Lili; Zhu, Nianfang; Cheng, Shulin; Tu, Yan; Yang, Yong
Abstract : This paper studies the influence of illumination level of modulated light on the visibility of the phantom array effect under office lighting condition. Results indicate that, the phantom array effect is comparable at different illumination levels when the modulated light is driven by 100Hz waveforms, while the phantom array is more visible at higher illumination levels with 600Hz waveforms.